The Evaluation of Students’ Prosocial Behavior On Primary Education Level - Setiawati, Esti; Ernawati, Ika (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2019)
This study aims to evaluate the prosocial behavior of elementary school level students, especially State Junior High School students in Bantul Regency. This research is  evaluation research with a quantitative descriptive approach with the CIPP (Context, Input, Process, and Product) model. The research subjects were 131 students of Bantul Regency Public Middle School. Data collection through the questionnaire, interviews, observation, and documentation methods. The results of this study indicate that in general the prosocial behavior of students in Bantul Regency State Junior High Schools was included in the quite good category. The results of this study also showed that the strengthening of the prosocial behavior of state junior high school students in the Bantul Regency was good enough as outlined in the school development program planning document and school activity plan